Estudo histoquímico e ultra-estrutural das fibras do sistema colágeno na glândula de veneno de Bothrops jararaca (Wied, 1824) (Reptilia, Squamata) - Murad, Luiza Helena Francescutti (1993)
It was studied through optical and eletronic transmission microscopy fragments of the main portion of the venom gland from Bothrops jararaca obtained at 6hs, 4, 8 and 45 days after manual extraction of the venom. The objective of this thesis was to identify some extracellular matrix components of the intertubular septa, in the different time setting of the cycle after venom extraction. Electron microscopic findings have confirmed the optical ones. After milking the secretory epithelium has changed to columnar as the venom synthesis cycle has begun. There was modification in the morphology of the connective septa with alterations in quantity and arrangement of collagen fibers. Thick collagen fibers were substituted by the fine reticular mesh in the intertubular stroma 6 hours after milking. At the 4th day of the cycle there was a rising in the number of type III fibers. Type I collagen fibers were found at the 8th after milking and their number was increased by day 45. The fibroblasts in those septa have shown morphologic modifications during the secretory cycle concomitant with alterations presented in the septal collagen fibers.